EFFECTS OF THE INDUCTION METHOD AND GAMIFICATION TECHNIQUES ON LEARNING ACHIEVEMENT AND MOTIVATION TOWARDS FOREIGN LOANWORDS IN THAI LANGUAGE GRADE 9 STUDENTS - Sohsuwan, Areeya; Rojrattanadamrong Chaisri, Rungarun (Journal of Education and Innovation, 2026)
The purposes of this research were 1) to compare students’ learning achievement on foreign loanwords in Thai language before and after learning through the inductive learning approach combined with gamification techniques 2) to compare students’ learning achievement on foreign loanwords in Thai language after the implementation of the inductive learning approach combined with gamification techniques with the criterion of 70 percent and 3) to compare students’ learning motivation toward foreign loanwords in Thai language before and after the implementation of the inductive learning approach combined with gamification techniques. The sample group consisted of students in Grade 9/1 at Nawaminthrachinuthit Satriwitthaya Phutthamonthon School, during the first semester of the 2025 academic year. The research instruments included lesson plans based on the inductive learning approach combined with gamification techniques, a Thai language learning achievement test, and a learning motivation questionnaire toward Thai language learning. The statistics used in this research included percentage, mean, and standard deviation, and inferential statistics, including a Dependent samples t-test and a one sample t-test. The findings revealed that 1) students’ learning achievement on foreign loanwords in Thai language after learning through the inductive learning approach combined with gamification techniques was significantly higher than before learning at the .05 level, 2) The students’ learning achievement in foreign loanwords in Thai language after the implementation of the inductive learning approach combined with gamification techniques was significantly higher than the 70 percent criterion at the .05 level and, 3) students’ learning motivation toward foreign loanwords in Thai language after the implementation of the inductive learning approach combined with gamification techniques was significantly higher than before learning at the .05 level.